Anda di halaman 1dari 21

IndefiniteIndefiniteIndefiniteIndefinite IntegralsIntegralsIntegralsIntegrals

IndefiniteIndefiniteIndefiniteIndefinite IntegralsIntegralsIntegralsIntegrals DefinitionDefinitionDefinitionDefinition

d

If dx [ g (x) ] = f (x), then g (x) + c is an indefinite integral of f (x) and

we write it as

e.g.

f (x) dx

= g (x) + c.

d

dx

( x

2

)

=

2x

2x dx

=

x

2

+

c

ImportanImportantImportanImportanttt

The results which are true for x are true for ax + b also ( as both are linear ), the only change is, obtained answer is to be divided by a ( i.e. coefficient of x )

ForForForFor exampleexampleexampleexample

sec

2 x dx = tan x + c

sec

2

 

x

2

 

dx

tan (x / 2)

=

1/ 2

+

c

=

2 tan

1

 

x

2

 

+

c

DifferentDifferentDifferentDifferent typestypestypestypes

TypeTypeTypeType –––– IIII

Sums based on standard result.

TypeTypeTypeType –––– IIIIIIII

Integrand of the type

P(x)

ax + b , where P (x) is a polynomial

Here divide numerator by denominator and use

dx log|ax

+ b |

=

ax

+

b

a

TypeTypeTypeType ---- IIIIIIIIIIII

+ c

IntegrationIntegrationIntegrationIntegration bybybyby substitutionsubstitutionsubstitutionsubstitution

f

'(

x

)

f

(

x

)

dx

= log

f

(

x

)

+ c

StandardStandardStandardStandard SubstitutionsSubstitutionsSubstitutionsSubstitutions

Expression

Substitution

2 2 a − x
2
2
a
− x

x

= a sin θ or x = a cos θ

2 2 a + x
2
2
a
+ x

x

= a tan θ or x = a cot θ

2 2 x − a
2
2
x
− a

x

= a sec θ or x = a cosec θ

a − x a + x
a
x
a
+
x

x

= a cos θ

2

TypeTypeTypeType –––– IVIVIVIV

a sin x

+

b cos x

csin x

+

d

cos x

 

+

B

d

dx

Integrals of the type

Here we write

Numerator =

A ( Denominator )

dx

and

a e

x

+

b

ce

x

+

d

( Denominator)

dx

Values of A and B are to be obtained by equating coefficients of sin x and cos x.

TypeTypeTypeType –––– VVVV

To express angle in numerator in terms of angle in the denominator. e.g.

To evaluate

sin ( x

a ) dx

a )

sin ( x

+

We write x – a = ( x + a ) – 2a

TypeTypeTypeType –––– VIVIVIVI

Integral of type

px

+

q

ax

2

+

bx

+

c

dx

Here we write

px

+

q

=

A

+

B

px + q OR ∫ dx OR ∫ 2 ax + bx + c d
px
+
q
OR
dx
OR
2
ax
+
bx
+
c
d
( ax
2 +
bx
+
c )
dx

P(x )

ax

2

+

bx

+

c

dx

In the third integral P(x) is a polynomial of degree greater than or equal to 2. Here, divide numerator by denominator and then proceed.

3

NoteNoteNoteNote : In CET, values of A and B can be obtained directly.

e.g. in

4x

+

3

x

2

+

2x

+

1

dx

As derivative of x 2 + 2x + 1 is 2x + 2 we write 4x + 3 = 2 ( 2x + 2 ) – 4 + 3 = 2 ( 2x + 2 ) – 1

TypeTypeTypeType –––– VIIVIIVIIVII (((( ImportantImportantImportantImportant ))))

Integral of the type

1

a + b sin x

Here we put

dx =

dx OR

tan

x

 

2

2dt

1

+

t

2

1

a + b cos x

dx OR

1

a + b sin x + ccos x

=

t

,

sin x

=

2t

1

+

t

2

, cos x

=

1

t

2

1

+

t

2

NoteNoteNoteNote ::::

If angle is 2x, put tan x = t

dx

=

dt

1

+

t

2

,

sin x

=

2t

1

+

t

2

, cos x

=

1

t

2

1

+

t

2

4

dx

TypeTypeTypeType –––– VIIVIIIVIIVIIIII Integral of the type

1

a + b sin

2

x

dx OR

1

a + b cos

2

x

dx OR

1

a + b sin

2

x + c cos

2

x

dx

Here we multiply numerator and denominator by sec 2 x and put tan x = t

NoteNoteNoteNote ::::

In the denominator

sin 2 x × sec 2 x = tan 2 x cos 2 x × sec 2 x = 1 sec 2 x = 1 + tan 2 x

TypeTypeTypeType –––– IXIXIXIX

IntegrationIntegrationIntegrationIntegration ByByByBy partspartspartsparts

The Theorem is

uv dx

=

u

v dx

 

du

dx

v dx

 

dx

This can be remembered as

fis – idfis Rule

The order in which u and v are to be taken is according to the serial order of the letters of the word “LIATE”, where

L : Logarithmic

I : Inverse Trigonometric

A

: Algebraic

T

: Trigonometric

E

: Exponential

5

TypeTypeTypeType –––– XXXX

Sums on

1.

2.

e

e

a x

a x

TypeTypeTypeType –––– XIXIXIXI

sin (

cos(

bx

bx

)

)

dx =

dx =

Sums based on

e

x

[f (x) + f '(x)] dx = e

e a x

(

a

sin

bx

b

cos

bx

)

+

c

(

a

cos

bx

+

b

sin

bx

)

+

c

a

2

+

b

2

 

a x

 

e

 

a

2

+

b

2

x

f (x) + c

Here multiple of e x is expressed as sum of a function and its derivative.

Typical sums of this type

log x

(1

+

log x )

2

dx ,

e

tan

1

x

1

+

x

+

x

2

1

+

x

2

 

6

dx

TypeTypeTypeType –––– XIIXIIXIIXII

PartialPartialPartialPartial FractionsFractionsFractionsFractions

1.1.1.1. DistinctDistinctDistinctDistinct LinearLinearLinearLinear FactorsFactorsFactorsFactors

ExampleExampleExampleExample

3x

+

5

x

2

+

2x

3

 

3x

+ 5

A

B

=

 

=

 

+

 
 
 

( x

1)( x

+

3)

( x

1)

( x

+

3)

We write 3x + 5 = A ( x + 3 ) + B ( x – 1 ) And so on

DisguisedDisguisedDisguisedDisguised linearlinearlinearlinear factorsfactorsfactorsfactors

ExampleExampleExampleExample

In

x

2

( x

2

+ 4)( x

2

7) we take x 2 = t for finding partial fractions

only. This is not a substitution.

2.2.2.2. RepeatedRepeatedRepeatedRepeated LinearLinearLinearLinear FactorsFactorsFactorsFactors

ExampleExampleExampleExample

x + 1

( x

1)

2

( x

+

2)

=

A

( x 1)

+

B

( x

1)

2

+

C

( x

+

2)

7

3.3.3.3. NonNonNonNon –––– repeatedrepeatedrepeatedrepeated quadraticquadraticquadraticquadratic factorfactorfactorfactor

ExampleExampleExampleExample

 

x

A

Bx

+

c

 

=

+

( 2x

+

1) ( x

TypeTypeTypeType –––– XIIIXIIIXIIIXIII

2

+ 3)

 

( 2x + 1)

 

( x

2

+

3)

ReductionReductionReductionReduction FormulaeFormulaeFormulaeFormulae

 

1.

sin

n

x dx

=

1

sin

n

1

x

cos

x

+

n

1

 

n

 

n

2.

cos

n

x dx

=

1

cos

n

1

x

sin

x

n

+

1

 

n

 

n

PollPollPollPoll QuestionQuestionQuestionQuestion

e log f (x)

= f (x)

8

sin

cos

n 2

n 2

x dx

x dx

ProofProofProofProof ::::

y

Let e

Put this in e

e

=

log

f (x)

y

log

=

e

f (x)

y

= f (x) to get

e

f (x)

= f (x)

SolvedSolvedSolvedSolved SumsSumsSumsSums

CETCETCETCET –––– 2008200820082008 (((( MemoryMemoryMemoryMemory BasedBasedBasedBased ))))

1.

 

3 dx

( x

2

+

1)( x

2

+

4)

=

(a) log ( x 2 + 1 ) – log ( x 2 + 4 ) + c

 

tan

1

x

1

tan

1

 

x

2

 

+

c

 
 

2

2 tan

 

1

x

tan

1

 

x

2

 

+

c

 
 

1

tan

1

x

tan

1

x

+

c

2

 

3 dx

 

=

 

=

( x

2

+

1)( x

2

+

4)

 

=

tan

 

1

1

 
 

 

dx

=

log x

(log x )

2

1

x

2

1

+

x

1

(b)

(c)

(d)

SolutionSolutionSolutionSolution

I

2.

9

1

2

1

x

2

x

2

tan

+

1

4

 

dx

 

+

c

(a)

1

log x

+ c

(b)

x + c log x
x
+ c
log x

(c)

x

(

log x

) 2

+ c

(d) log x + c

SolutionSolutionSolutionSolution

I

=

1

1

log x

(log x )

2

dx

Put log x = t

∴ x = e t

∴ dx = e t dt

e

t

1

t

1

t

2

dt

=

e

t

1

+

c

 

t

e

x

(x

+

2

2)

 

( x

+

2)

3

x

I

=

 

+

c

 
 

e

x

 

(

x

+

2

)

2

+ c

 

x e

x

(

x

+

2

)

2

+ c

 
 

x

1

=

e

(x

+

2)

2

 

e

x

(

x

+

2

)

2

+ c

 
 

1

1

 

(b)

ab

sin

 

 

1

 

1

 

(d)

ab

sin

 

=

log x

(b)

(d)

dx

=

3.

x e

+

( x

x

2)

3

dx =

 

e

x

 

(a)

x

+

2 +

c

 

e

x

 

(c) (

x

+

2

)

3

+ c

SolutionSolutionSolutionSolution

 
 

I

=

x e

+

( x

x

2)

3

dx

=

ax

b

bx

a

1 ∫ 2 2 2 a − b x
1
2
2
2
a
b
x

(a)

(c)

dx =

4.

1

1

bx

+

 
 

sin

 

c

b

a

1

1

ax

+

 
 

sin

 

c

b

b

10

2

( x

+

+

+

c

c

2)

3

dx

SolutionSolutionSolutionSolution

 

 

1

1

 

I

=

2 2 2 a − b x
2
2
2
a
b
x

dx

=

b

 

=

1

sin

 

b

5.

x

+

1

x

n

dx =

 

(a)

 

1

log | x

n

+

1

+

1|

+

 

n

+

1

   

c

 

(c)

n

1

+

1

log | x

n

|

+

c

SolutionSolutionSolutionSolution

 
 

I

=

x

+

1

x

n

dx

=

1

x +

1

 

n

 

x

 

=

1

(n

+

1 ) x

n

dx

 
 

n

+

1

x

n

+

1

+

1

 

=

n

1

+

1

log | x

n

+

1

+

1|

+

c

1

dx

2  a  2 − x   b  
2
a
2
− x
 
b
 

1

 

bx

 

+

c

 

a

 

(b)

1

n

log | x

(d)

1

log | x

n

 

n

=

x

n

+

1

dx

x

+

1

dx

CETCETCETCET –––– 2009200920092009 (((( MemoryMemoryMemoryMemory Based)Based)Based)Based)

1.

e

(a)

x

1

x

x

2

e

x

x

2

+ c

dx =

(b)

e

x

x

+ c

11

(c)

x e

x

+ c

n |

n

+

+

1

|

c

+ c

(d)

e

x

x

2

+ c

SolutionSolutionSolutionSolution

x

1

x

1

x

2

e

x

 

1

×

+

c

 

x

(b)

x

2

(

2 log x

1

)

+

 

4

c

(d)

x

4

(

2 log x

+

1

)

+

c

1

x

 

x

2

 

×

 

2

1

×

x

2

=

x

2

(

2 log x

1

)

+

2

2

4

   

I

=

dx

=

e

x log x dx =

x

4

x

2

(

4

2 log x

(

2 log x

1

+

x log x dx

=

=

)

1

=

+

)

c

+

c

2.

(a)

(c)

SolutionSolutionSolutionSolution

I =

log x . x dx

2

×

x 2

2

log x

x

2

log x

CETCETCETCET –––– 2010201020102010 (((( MemoryMemoryMemoryMemory BasedBasedBasedBased ))))

dx

1.

16 x

1

4

1

3

2

+

tan

tan

9

1

1

(a)

(c)

SolSolutionSolSolutionutionution

=

 

4x

3

4x

 

3

+

+

c

c

(b)

(d)

1

1

4x

+

 
 

tan

 

c

 

12

3

 

tan

1

4x

 

3

+

c

12

c

I =

dx

 

=

1

dx

 

16 x

2

+

9

16

x

2

+

9

 

16

 

1

1

=

×

tan

16

1

3

4

1

4x

=

12

tan

3

1

+ c

x

3/ 4

+ c

2.

e

tan x

(sec

2

x + sec

3

(a) e x sec x tan x + c

(c) e tan x sec 2 x + c

x sin x ) dx =

e tan x . tan x + c

(b)

(d) e tan x . tan 2 x + c

SolutionSolutionSolutionSolution

e

tan x

(sec

2

put tan x = I

t

e

x

( t

=

x

+

sec

sec

+

1) dt

2

3

x sin x ) dx

=

e

tan x

2

x ( 1

=

sec

+

sec x sin x ) dx

2

x dx

e

tan x

. tan x

( 1

+

tan x)sec

+

c

x dx

=

=

e

t

. t

dt

=

e

tan x

MoreMoreMoreMore SolvedSolvedSolvedSolved SumsSumsSumsSums

1.

e

5 log

x

e

4 log

x

e

3 log

x

e

2 log

x

dx

(a) log | x 3 – x 2 | + c

(c) 2 x + c

(b)

3 x + c 3
3
x
+ c
3

(d) log | x ( x – 1 ) | + c

13

SolutionSolutionSolutionSolution

 

e

log x

5

-

e

log x

4

e

log x

3

-

e

log x

2

log f

(

x

)

=

f

x

( )

   

x

5

-

x

4

x

4

(

x

-

1

)

 

=

ò

 
 

x

3

-

x

2

x

2

(

x

-

1

)

ò

2

dx

 

x

3

x

=

 

3

ò

I =

using e

I ò

=

=

2.

cos 2

cos 2 x

α

cos

x

cos

α

dx

is

(a) sin x – x sin α + c

(c)

2 ( sin x + x cos α ) + c

SolutionSolutionSolutionSolution

(b) x cos α + cos x + c (d) cos x + x sin α + c

I

=

2cos

2

x

1

(

2cos

2

α −

1

)

cos x

cos

α

dx

2 =

(

cos

2

x

cos

2

α

)

dx

 
 

cos x

cos

α

 

= 2

(

cos x

 

+

cos

α

) (

cos x

cos

α

)

 
   

cos x

cos

α

 

= 2

(

cos x

+

cos

α

)

dx

=

2

(

sin x

+

x cos

α

)

+

c

=

2

(

sin x

3.

∫ 1 + 2 tan x(sec x + tan x) dx is 3 3/2 (a)
1 + 2 tan x(sec x + tan x) dx
is
3
3/2
(a)
[1
+
2 tan
x
(sec
x +
tan
x
)]
+ c
2
(b)
log sec x ( sec x + tan x ) + c

(c)

(d)

log sec x - log sec x + tan x + c

log sec x + tan x + c

14

+

x cos

α

)

+

c

SolutionSolutionSolutionSolution

2 I 1 = ∫ + 2 tan x sec x + 2 tan x
2
I 1
=
+
2 tan x sec x
+
2 tan
x
(
2
)
2
=
1
+
tan
x
+
2sec x tan x
+
tan
x
2
2
=
sec
x
+
2sec x tan x
+
2 tan
x dx
2
=
(
sec x
+
tan x
)
dx
=
(
sec x
+
tan x
)
=
log
[
sec x
+
tan x
]
+
log
[
sec x
]
+
c
=
log
sec x
(
sec x
+
tan x
)
1
+  
c
 
sin 2 x dx
4.
=
4
4
∫ cos
x +
sin
x

dx

(a)

(c)

SolutionSolutionSolutionSolution

log

+ cx dx (a) (c) SolutionSolutionSolutionSolution log tan – 1 ( tan 2 x ) + c

tan – 1 ( tan 2 x ) + c

(b) cot – 1 ( tan x ) + c

(d) 2 tan – 1 ( tan x ) + c

I

=

2sin x cos x

cos

4

x

+

sin

4

x

dx

Divide Numerator and Deno min ator by cos sin x

1

dx

2

cos x

cos

2

x

I

+

2 tan x sec

1

tan

4

x

2

x dx

2

(

x

tan

=

t

2

x

)

2

+

1

=

=

=

put tan

2 tan x sec

4 x

2 tan x sec
2 tan x sec

2 tan x sec

tan

4

2

x

+

x dx

1

2

x dx

=

dt

I

=

dt

t

2

+

1

=

tan

1

(

t

)

+

c

=

tan

1

(

tan

2

x

)

+

c

5.

cos

sin sin 2 x

x

x dx

1

+

15

(a)

(c)

SolutionSolutionSolutionSolution

1

+ c

+ sin

cos

x

x

1

+ c

sin 2 x

put

cos x

+

sin x

=

t

(

1

)

(

sin x

+

cos x

)

dx

=

dt

(

on squaring 1

)

 

cos

2

x

+

sin

2

x

+

1

+

sin 2 x

=

t

2

I

=

dt

t

2

=

t

2

dt

 

I

=

t

1

=

1

 

1

 

cos x

+

sin x

 

log(

x +

2)

log

x dx

 

6.

 
 

x

(

x +

2)

 

2 sin x cos x

+ c

(a)

(c)

SolutionSolutionSolutionSolution

2 1  x + 2  log +   4 x  
2
1
x
+ 2
log
+
4
x
2
− 1 
x + 2
log
4
x

c

+ c

=

t

16

2

(b)

(d)

(b)

(d)

1

cos

x

1

sin

x

+ c

cos 2 x

+ c

[log(x + 2) – log x ] 2 + c

[log(x + 2) – log x ] + c

put log ( x + 2 ) − log x = dt  1 1
put log
(
x
+
2
)
log x
=
dt
1
1
d x
=
dt
x
+
2
x
x
x
2
dx
=
dt
x
(
x
+
2
)
dx
1
=
dt
x
(
x
+
2
)
2
2
1
1
t
I
=
t
×
dt
=
×
2
2
2
− 1
2
=
 log
x
+
2
− log
x
+ c
 
4
2
− 1 
x
+
2
=
log
+ c
4
x

7.

dx

cos(

x a

)cos(

x b

)

=

(a) log cos ( x – a ) cos ( x – b ) +c

(b) log

tan( x − a ) tan( x − b )
tan(
x
− a
)
tan(
x
− b
)

+ c

(c)

(d)

sin(

1

a

b

)

log

cos( x − a ) cos( x − b )
cos(
x
a
)
cos(
x
b
)

+ c

 

1

log

cos(

x

a

)

+ c

cos(

a

b

)

cos(

x

b

)

SolutionSolutionSolutionSolution

 

I =

 

1

sin

(

x

b

)

 

(

x

a

)

 

sin

(

a

b

)

cos

(

x

a

)

cos

(

x

b

)

 
 

=

1

sin

(

x

b

)

cos

 

(

x

a

)

cos

(

x

b

)

sin

(

x

a

)

 

sin

(

a

b

)

 

cos

(

x

a

)

cos

(

x

b

)

 

=

sin

(

1

a

b

)

(

tan

(

x

b

)

tan

(

x

a

))

dx

 

=

1

log

sec

<